Online Peer Feedback on English Writing: The Economics Students’ Voices - Sufiyandi, Sufiyandi; Emilia , Emi; Damayanti , Ika Lestari; Maisarah , Ira (Journal of English Education and Teaching, 2025)
Online peer feedback on writing has been studied by many scholars to examine the applications, the effectiveness, the weaknesses, and the students' perceptions in the context of learning English for general purposes, but little attention has been paid to its use in the area of English for specific purposes. The present study aims to reveal the Economics students’ experiences with the use of online peer feedback in writing. This study was designed as a mixed-method inquiry that involved 140 Economics students at a university in Bengkulu Province, Indonesia, who took English courses. The data was gathered using a questionnaire and a semi-structured interview, which were analyzed based on each type, quantitatively and qualitatively, to reach the objective of the study. The results show that economics students viewed the use of online peer feedback in writing activities very positively. The results of this research contribute theoretically and practically to encouraging the use of online peer feedback in improving student effectiveness and skills.